A novel plasma lncRNA ENST00000416361 is upregulated in coronary artery disease and is related to inflammation and lipid metabolism - Li, Ping; Yan, Xinxin; Xu, Guidong; Pang, Zhi; Weng, Jiayi; Yin, Juan; Li, Meifen; Yu, Lan; Chen, Qian; Sun, Kangyun (Molecular medicine reports, 2020)
Coronary artery disease (CAD) is a serious threat to human health and a major cause of mortality worldwide. Long noncoding RNAs (lncRNAs) affect the occurrence and development of CAD via the regulation of cell proliferation and apoptosis, inflammatory responses and lipid metabolism. Screening methods and therapeutic strategies for CAD have been extensively studied. The present study analyzed clinical indexes of 187 patients with CAD and 150 healthy subjects. The data showed significant differences in diabetes mellitus, hypertension, high‑density lipoprotein level and smoking history between the CAD group and the control group. A series of differentially expressed lncRNAs were detected in the plasma samples of three patients with CAD by high‑throughput sequencing. Reverse transcription‑quantitative (RT‑q)PCR data revealed that the expression level of the novel lncRNA ENST00000416361 was ~2.3‑fold higher in the plasma of 50 patients with CAD compared with the 50 control subjects. Receiver operating characteristic (ROC) curves were generated, and the area under the ROC curve was 0.7902. Knockdown of ENST00000416361 in human umbilical vein endothelial cells markedly downregulated interleukin‑6 and tumor necrosis factor‑α levels. In addition, sterol regulatory element binding transcription factor (SREBP)1 and SREBP2 were upregulated in patients with CAD, and they were positively correlated with the expression of ENST00000416361. RT‑qPCR further demonstrated that knockdown of ENST00000416361 led to the downregulation of SREBP1 and SREBP2. Overall, the novel lncRNA ENST00000416361 may be associated with CAD‑induced inflammation and lipid metabolism, and it may serve as a potential biomarker for CAD.